Mathematics Anxiety And Stress Coping Strategies Among Preservice Mathematics Teachers - Ikrimah, Ikrimah; Juliadarma, Minggusta; Sitifatima Abubakar, Sitifatima Abubakar3; Kisman, Abida (Universitas Islam Ahmad Dahlan (UIAD), 2025)
Although numerous studies have examined mathematics anxiety among preservice teachers, research focusing on its association with stress coping strategies remains limited. This study collected data on mathematics anxiety and stress coping from 211 preservice mathematics teachers to investigate whether differences in mathematics anxiety exist based on the coping strategies they employed. A quantitative approach with a cross-sectional design was applied. The instruments included the Revised Mathematics Anxiety Survey (R-MANX) to assess mathematics anxiety and a stress coping questionnaire based on Lazarus and Folkman’s theory, categorized into Problem-Focused Coping (PFC) and Emotion-Focused Coping (EFC). Data were analyzed using descriptive statistics, cross-tabulation, and the Kruskal–Wallis H test. The findings revealed that most preservice mathematics teachers experienced moderate levels of mathematics anxiety. The majority of respondents predominantly relied on Emotion-Focused Coping (EFC) to manage stress, and this tendency was consistent across all levels of anxiety—low, moderate, and high. Although descriptive results indicated differences in coping preferences, statistical analysis showed no significant differences in mathematics anxiety across coping strategy types. Therefore, it can be concluded that coping strategies did not emerge as significant differentiating factors for mathematics anxiety among preservice mathematics teachers in this study